Pengaruh kompres hangat dan pijat effleurage terhadap nyeri dismenorea pada remaja putri - Dian Suhartini; Hidayani Hidayani; Ratna Wulandari (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2022)
Backgrounds: Dysmenorrhea that occurs in women is still a problem, especially in adolescents because many teenagers experience dysmenorrhea in the first three years after menarche. Purpose: The purpose of this study was to determine the effect of warm compresses and effleurage massage to dysmenorrhea pain in adolescent girls at Junior High School No 1 Pulosari, Pandeglang Regency in 2022. Methods: This study used a quantitative design using a quasi-experimental two group comparison pretest-posttest design. with a population of 30 people who experienced dysmenorrhea that divided into a control group and the experimental group using total sampling. The research instrument used the Visual Analog Scale (VAS) pain observation sheet. Results: The results of the study in both groups showed that there was an effect of warm compresses and effleurage massage on dysmenorrhea pain. The results of the paired t-test found that p = 0.000 < 0.05. The results of the independent sample t-test found the p = 0.019. There was a significant difference of pain between warm compresses and effleurage massage groups. warm compresses is more effective in reducing the pain of dysmenorrhea compared to effleurage massage. Warm compresses or effleurage massage can be used to reduce the pain of dysmenorrhea experienced by adolescents.    Pendahuluan: Dismenorea yang terjadi pada wanita sampai saat ini masih menjadi masalah, khususnya pada remaja karena banyak remaja mengalami dismenorea pada tiga tahun pertama setelah menarche. Tujuan: Untuk mengetahui pengaruh pemberian kompres hangat dan massage effleurage terhadap nyeri dismenorea pada remaja putri di SMP Negeri 1 Pulosari Kabupaten Pandeglang tahun 2022. Metode: Penelitian ini menggunakan desain kuantitatif dengan metode quasi eksperimental two group comparison pretest-posttest design. dengan populasi yang mengalami dismenorea sebanyak 30 orang terbagi menjadi kelompok kontrol dan kelompok eksperimen menggunakan total sampling serta instrumen penelitian menggunakan lembar observasi nyeri Visual Analog Scale (VAS). Hasil: Hasil Penelitian pada kedua kelompok menunjukkan adanya pengaruh kompres hangat dan massage effleurage terhadap nyeri dismenorea dengan hasil uji paired sample T Test p=0,000 < 0,05. Hasil uji independent sample t-test p=0,019 ada perbedaan signifikan antara kelompok kompres hangat dan massage effleurage. Kompres hangat lebih efektif menurunkan nyeri dismenorea dibandingkan dengan massage effleurage. Kompres hangat atau massage effleurage dapat digunakan untuk mengurangi nyeri dismenorea yang dialami oleh remaja.